Intelligent organisation of semantic networks, DIME network architecture and grid automata. (2016) - Burgin, Mark; Mikkilineni, Rao; Morana, Giovanni
A network architecture, based on increasing intelligence of computing nodes, is suggested for building the semantic grid. In its essence, distributed intelligent managed element (DIME) network architecture extends the conventional computational model of information processing networks, allowing improvement of the efficiency and resiliency of computational processes. This approach is based on organising the process dynamics under the supervision of intelligent agents. The DIME network architecture utilises the DIME computing model with non-von Neumann parallel implementation of a managed Turing machine cluster with a signalling network overlay and adds cognitive elements to evolve super-recursive information processing, for which it is proved that they improve efficiency and power of computational processes. In this paper, we model the DIME network architecture using grid automata. A grid automaton provides a universal model for computer, sensor, and many other networks. We introduce different types of grid automata and study constructive operations with grid automata, which are oriented at the network construction, generation and development.